Faces of precarity : critical perspectives on work, subjectivities and struggles - Choonara, Joseph; Murgia, Annalisa; Carmo, Renato Miguel do, 1971- (Bristol University Press, 2022)
The word 'precarity' is widely used when discussing work, employment or social classes. However, there is no consensus on the precise meaning of the term or how it should best be used to explore social changes. This international and interdisciplinary book offers a distinctive and critical perspective approach to an important topic.